Evaluación del rol de las empresas del sector de la construcción en el proceso de reactivación económica de la ciudad de Bogotá d.C. entre los años 2019 al 2021 (2021)
The construction sector has been one of the most important in the city due to its impact on the local economy, generating jobs and promoting economic movements in other sectors directly or indirectly. Like the other economic sectors, it has also been greatly affected by the COVID 19 pandemic, thus creating enormous challenges to achieve a progressive and continuous economic reactivation; during this time of pandemic it has generated uncertainty regarding the local and national economy, being Bogota the capital of the country, which in its economic movements had a greater impact so measures have been taken to maintain commercial operations in a minimum of execution; this in order to ensure that the economy does not stop completely.